Facts about Wildlife Diseases: Antler Infections and Cranial Abscess Disease in White-Tailed Deer: VM260, 1/2024 - Lyons, Michael A.; Richardson, Amira M.; Urban, Merrie P.; Campos Krauer, Juan M. (EDIS, 2024)
This article provides valuable insights into antler infections and cranial abscess disease in white-tailed deer. It emphasizes the importance of addressing these concerns for the species’ conservation and well-being. Written by Michael A. Lyons, Amira M. Richardson, Merrie P. Urban, and Juan M. Campos Krauer, and published by the Veterinary Medicine—Department of Large Animal Clinical Sciences, UF/IFAS Extension, January 2024.